Baselines Issues In Determining The Delimitation Of Indonesia's Maritime Boundaries With Neighboring States - Evi Purwanti; Radifan Anhari (Faculty of Law, Universitas Pekalongan, 2025)
Maritime boundaries play a strategic role in determining a state's sovereignty limits, managing natural resources, and maintaining national security and stability. The establishment of a baseline is a crucial element in maritime boundary delimitation, especially for archipelagic states such as Indonesia. This study aims to identify the legal effects of the baseline and analyze the challenges Indonesia faces in applying the maritime delimitation provisions under the 1982 United Nations Convention on the Law of the Sea (UNCLOS). Based on the analysis, the findings reveal two primary factors influencing Indonesia's application of baseline provisions under UNCLOS 1982. First, the supporting factors include: the legal certainty of a maximum 12-nautical-mile territorial sea; the legal guarantee for the exploration and exploitation of marine natural resources that better fulfills the element of equity for developing countries; and UNCLOS 1982’s flexibility in accommodating the geographical and geological uniqueness of coastal states through various baseline classifications and state types. Second, there are challenges in implementation, including: vague interpretations of several UNCLOS provisions, which lead to divergent state practices in drawing baselines; the absence of sanctions or formal reprimands for violations, leaving such deviations uncorrected unless resolved through international adjudication; and technical inconsistencies in determining maritime boundary coordinates, which complicate consensus between neighboring states. This study underscores the importance of adopting innovative legal approaches and enhancing coordination among national and international institutions to ensure the legitimate and sustainable enforcement of Indonesia’s maritime boundaries.